The eBay millionaire : - Joyner, Amy (J. Wiley, 2005)
Within every information-packed page, author Amy Joyner goes one-on-one with eighteen Titanium PowerSellers to reveal the proven and tested strategies that will enable you to build your own profitable eBay business. While the book begins with some general guidance on getting your eBay venture up and running, it quickly moves on to profile eBay's top merchants—those collectively moving millions of dollars in goods every year. This diverse group, which sells everything from restaurant refrigerators to designer shoes, shares their exclusive and invaluable experiences.